1996
DOI: 10.1111/j.1476-5381.1996.tb16066.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the inwardly‐rectifying current in the smooth muscle cells of the rat bladder

Abstract: 1 In freshly-isolated single cells of the rat bladder detrusor, outwardly-rectifying and inwardlyrectifying membrane currents were identified by the whole-cell voltage-clamp technique. 2 The inwardly-rectifying current (IIR) exhibited features of a cation current permeable to both K+ and Na+ but it was unaffected by changes in extracellular Ca2 . It had an activation threshold close to -60 mV and an estimated reversal potential of -29 mV.3 IIR activated slowly with a voltage-sensitive time-constant of 69 ms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…In rat UBSM cells an inward cation current demonstrating a slow time-dependent activation (time constant ϳ200 ms at Ϫ100 mV) on hyperpolarization and block by 1 mM Cs ϩ has been reported (12). Green and colleagues (12) concluded that this cation current was similar to the hyperpolarization-activated cation current (I h ) extensively characterized in cardiac myocytes and neurons (32).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In rat UBSM cells an inward cation current demonstrating a slow time-dependent activation (time constant ϳ200 ms at Ϫ100 mV) on hyperpolarization and block by 1 mM Cs ϩ has been reported (12). Green and colleagues (12) concluded that this cation current was similar to the hyperpolarization-activated cation current (I h ) extensively characterized in cardiac myocytes and neurons (32).…”
Section: Discussionmentioning
confidence: 94%
“…6 -8) and demonstrates an insensitivity to blockade by 2 mM external Cs ϩ (n ϭ 3). Moreover, Green and colleagues (12) used leak subtraction in their study, eliminating any time-independent background currents, such as the UBSM I cat described here. 9.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, I h was also found in some other tissues such as B cells of pancreatic Langerhans islets (134), enteric (37,179,429), lymphatic smooth muscle (254), uterine smooth muscle (296), smooth muscle cells of the bladder (163) or portal vein (164), testis (341), and the enteric nervous system (427). However, HCN channel transcripts have only been reported in some of these tissues or cell types (134,164,341,427).…”
Section: Tissue Expression Of Hcn Channelsmentioning
confidence: 99%
“…In spite of many in vitro reports on Ih channels (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) as well as in vivo studies on the pacemaking function of Ih (25)(26)(27)(28), any contributions of Ih to epileptic activity are unknown in vivo, except for the one that showed the long-lasting enhancement of the widely expressed intrinsic Ih that converts the potentiated synaptic inhibition to hyperexcitability in the hippocampus of rats that had febrile seizures (29).…”
mentioning
confidence: 99%